2008
DOI: 10.1016/j.ejcts.2007.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar resections in stage IA non-small cell lung cancer: segmentectomies result in significantly better cancer-related survival than wedge resections☆

Abstract: Studies investigating survival after sublobar resection of stage IA NSCLC should always distinguish between anatomical segmentectomies and wedge resections. If limited functional operability requires a sublobar resection of stage IA NSCLC, segmentectomy with systematic lymphadenectomy should be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 17 publications
3
111
0
6
Order By: Relevance
“…Two reports present retrospective comparisons of segmentectomy and wedge resection [43,44]. The report by EL-SHERIF et al [43] focuses on the relationship between resection margin and local recurrence in patients with stage I nonsmall cell lung cancer who underwent either segmentectomy or wedge resection.…”
Section: Segmentectomy Versus Wedge Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reports present retrospective comparisons of segmentectomy and wedge resection [43,44]. The report by EL-SHERIF et al [43] focuses on the relationship between resection margin and local recurrence in patients with stage I nonsmall cell lung cancer who underwent either segmentectomy or wedge resection.…”
Section: Segmentectomy Versus Wedge Resectionmentioning
confidence: 99%
“…In the series of EL-SHERIF et al [43], resection margins had no impact on regional or distant recurrence. In the study of SIENEL et al [44], 56 patients underwent segmentectomy with systematic nodal dissection and 31 underwent wedge resection with selective nodal sampling at the surgeon's discretion for stage I nonsmall cell lung cancer. Sublobar resections were indicated because of cardiopulmonary impairment.…”
Section: Segmentectomy Versus Wedge Resectionmentioning
confidence: 99%
“…There are several facts that may explain this worse prognosis. Segmentectomies are associated with a significant better cancer-related survival than that of wedge resections in patients with stage IA tumours, even when the subgroup of tumours ≤2 cm in size is analysed independently; and recurrence is significantly lower for segmentectomies (12). Recurrence is significantly higher when the resection margin is <1 cm and this is found more frequently in wedge resections than in segmentectomies (13).…”
mentioning
confidence: 83%
“…Recurrence is significantly higher when the resection margin is <1 cm and this is found more frequently in wedge resections than in segmentectomies (13). This may be because other sites of field cancerization in the same lobe are not included in the resected specimen, to STAS, as described above, or to suboptimal intraoperative nodal assessment, which tends to be more limited in wedge resections (12). There is no doubt that segmentectomies and wedge resections are different operations that we tend to put together in the same box.…”
mentioning
confidence: 87%
“…In these trials, selection for limited resection includes tumors 2 cm or less in size, peripheral tumors close to the outer third of the lung and good functional status. Finally, sub-lobar resection should preferably be performed by a segment and not by a wedge resection as current data in early stage NSCLC patients revealed that a segment resection is associated with a higher cancer-related survival and lower local recurrence rate compared with a wedge resection [36] .…”
Section: Nsclc Stagementioning
confidence: 99%